ANALISIS FILM ANIMASI JUMBO DALAM PENANAMAN NILAI KARAKTER PADA ANAK USIA DINI - Nurmailis, Nurmailis; Aviatri, Yudha (Bunayya, 2025)
The Indonesian animated film Jumbo, released after Eid al-Fitr 2025, is worth examining not only for its popularity as a family movie but also for its emphasis on character values. This study uses a literature review approach for data collection and applies narrative synthesis based on Popay et al. (2006) to analyze the film’s content and meaning. The findings reveal that film is an effective medium for instilling character values in early childhood. Jumbo conveys messages of friendship, perseverance, good listening, creativity, and gratitude through a storyline that resonates with children’s everyday experiences. These values support children’s understanding of right and wrong (Kohlberg, 1984), while also fostering the development of moral reasoning and behavior aligned with social norms.